2010
DOI: 10.1002/jcp.22252
|View full text |Cite
|
Sign up to set email alerts
|

C2 and C2C12 murine skeletal myoblast models of atrophic and hypertrophic potential: Relevance to disease and ageing?

Abstract: Reduced muscle mass and increased susceptibility to TNF-induced degradation accompany inflamed ageing and chronic diseases. Furthermore, C(2) myoblasts display diminished differentiation and increased susceptibility to TNF-alpha-induced cell death versus subcloned C(2)C(12) cells, providing relevant models to assess: differentiation (creatine kinase), growth (protein), death (trypan-blue) and anabolic/catabolic parameters (RT-PCR) over 72 h +/- TNF-alpha (20 ng ml(-1)). At 48 and 72 h, respectively, larger myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 59 publications
7
70
0
1
Order By: Relevance
“…2c). These data are consistent with observations in other in vitro models (Langen et al 2001;Sharples et al 2010;Strle et al 2004;te Pas et al 2000) and indicate that the reduced expression of these markers is responsible for the loss of differentiation capacity in C2C12BKD cells (Table 2: differentiation markers). Baker et al reported that expression of p16 Ink4a in BubR1 hypomorphic mice plays a key role in the development of age-related disorders including sarcopenia (Baker et al 2008(Baker et al , 2011.…”
Section: Bubr1 Hypomorphic C2c12 Cells Show Impaired Myogenic Differesupporting
confidence: 92%
See 2 more Smart Citations
“…2c). These data are consistent with observations in other in vitro models (Langen et al 2001;Sharples et al 2010;Strle et al 2004;te Pas et al 2000) and indicate that the reduced expression of these markers is responsible for the loss of differentiation capacity in C2C12BKD cells (Table 2: differentiation markers). Baker et al reported that expression of p16 Ink4a in BubR1 hypomorphic mice plays a key role in the development of age-related disorders including sarcopenia (Baker et al 2008(Baker et al , 2011.…”
Section: Bubr1 Hypomorphic C2c12 Cells Show Impaired Myogenic Differesupporting
confidence: 92%
“…Figure 2b illustrates the significant difference in fusion index between C2C12 and C2C12BKD cells from day 7 onward. In the two other in vitro models, using TNF-a-and dexamethasone-treated C2C12 cells, myotube formation was decreased in the differentiation medium but was not absent (Langen et al 2001;Sharples et al 2010;te Pas et al 2000) (Table 2: myotube formation). In contrast, in C2C12BKD cells myotube formation was essentially abolished.…”
Section: Bubr1 Hypomorphic C2c12 Cells Show Impaired Myogenic Differementioning
confidence: 96%
See 1 more Smart Citation
“…Our group has further begun to elucidate potential epigenetic modulators of myoblast survival and differentiation (Saini et al2012), where activation of Sirtuin1 (histone deacetylase) reduced myoblast death and enabled differentiation in the presence of stress from TNF-α, a cytokine that is chronically up regulated in muscle loss conditions such as sarcopenia and cachexia. We have extensively shown that TNF-α impairs myoblast fusion/differentiation and myotube hypertrophy with corresponding reductions in myoD gene expression in mouse and human muscle cells (Meadows 2000;Foulstone 2001Foulstone , 2004Al-Shanti 2008;Saini 2008;Sharples 2010). Thus, together with the above studies, this perhaps provides compelling yet preliminary data suggesting that epigenetic mechanisms such as myoD methylation could be involved in TNF-α induced reduction in differentiation and myotube atrophy in muscle cells and potentially be involved in muscle cell programming/memory.…”
Section: Introductionmentioning
confidence: 99%
“…Higher TNF-α levels are strongly correlated with muscle loss, reduced strength and therefore morbidity and earlier mortality. We have extensively shown that TNF-α impairs regenerative capacity in mouse and human muscle derived stem cells (Meadows 2000;Foulstone 2001Foulstone , 2004Al-Shanti 2008;Saini 2008;Sharples 2010). We have also recently established an epigenetically mediated mechanism (SIRT1-histone deacetylase) regulating survival of myoblasts in the presence of TNF-α (Saini 2012).…”
mentioning
confidence: 99%